ANALISIS VEGETASI MANGROVE DAN PEMANFAATANNYA OLEH MASYARAKAT KAMPUNG ISENEBUAI DISTRIK RUMBERPON KABUPATEN TELUK WONDAMA - Yan F.A. Auri; Jan H. Nunaki; M.J. Sadsoeitoeboen (FMIPA Universitas Papua, 2008)
The objective of this research was to know the structure, composition, potency of mangrove tree and also exploitation of mangrove observation type in Isenebuai Village District Rumberpon Teluk Wondama. Vegetation observation was conducted using line and plot method and the interview technique flourish structure. The result of analyse vegetasi study show that 11 mangrove plant species from 5 families were found.The 11 species are Aegiceras corniculatum, Bruguiera sylindrica, Bruguiera gymnorrhiza, Rhizophora stylosa ,Rhizophora mucronata, Ceriops tagal, Heritiera littoralis, Heritiera globosa, Lumnitzera litorea, Xylocarpus granatum and Xylocarpus moluccensis. The result also show that local people used 7 mangrove plant species from 4 families for 7 categories of use that are food-stuff, construction material, medicine, energy sources, boat supply, musical instrument and equipments of artistry and furniture.